Normal-relaxor ferroelectric phase transition induced morphotropic phase boundary accompanied by enhanced piezoelectric and electrostrain properties in strontium modulated Bi0.5K0.5TiO3 lead-free ceramics. Issue 12 (September 2020) - Li, Feng; Wu, Shuanghao; Li, Tianyu; Wang, Chunchang; Zhai, Jiwei
Abstract: In this work, (Bi0.5 K0.5 )1-x Srx TiO3 compositions (x = 0.03∼0.18) are designed to clarify the role of normal-relaxor ferroelectric phase transition and morphotropic phase boundary on dielectric, piezoelectric and electrostrain properties. With increasing strontium content, tetragonal distortion decreases and tetragonal and pseudocubic phases coexist in 0.09 ≤ x ≤ 0.15 compositions; the spontaneous phase-transition temperature and curie temperature decrease, as certified by phase-structure, dielectric properties and Raman spectra analysis. Optimized piezoelectric constant ∼106 pC/N and electrostrain ∼0.17 % are obtained for (Bi0.5 K0.5 )0.88 Sr0.12 TiO3 composition. Piezoelectric force microscopic technique is exploited to clarify the origin of enhancement in macroscopic performances. Increase in temperature enhances ferroelectric performance and a large strain value ∼0.25 % with low hysteresis ∼27 % are obtained at 140 °C for the optimized composition, which are believed to originate from electric-field induced relaxor-to-ferroelectric phase transition with thermally-activated reduced energy barriers. This work clearly demonstrates that lead-free Bi0.5 K0.5 TiO3 -based ceramics are another promising bismuth-based species in applications of piezoelectric sensors and actuators.